SNG and DNG meta-absorber with fractional absorption band for sensing application - Ahasanul Hoque (Nature Portfolio, 2020)
Abstract This paper reports on a tunable transmission frequency characteristics-based metamaterial absorber of an X band sensing application with a fractional bandwidth. Tunable resonator metamaterial absorbers fabricated with dielectric surface have been the subject of growing attention of late. Absorbers possess electromagnetic properties and range modification capacity, and they have yet to be studied in detail. The proposed microstructure resonator inspired absorber with triple fractional band absorption consists of two balanced symmetrical vertical patches at the outer periphery and a tiny drop hole at two edges. Experimental verification depicted two absorption bands with single negative (SNG) characteristics for two resonances, but double negative (DNG) for single resonance frequency. The mechanism of sensing and absorption was analyzed using the transmission line principle with useful parameter analysis. Cotton, a hygroscopic fiber with moisture content, was chosen to characterize the proposed absorber for the X band application. The electrical properties of the cotton changed depending on the moisture absorption level. The simulation and the measured absorption approximately justified the result; the simulated absorption was above 90% (at 10.62, 11.64, and 12.8 GHz), although the steady level was 80%. The moisture content of the cotton (at different levels from 0 to 32.13%) was simulated, and the transmission resonance frequency changed its point in two significant ranges. However, comparing the two adopted measurement method and algorithm applied to the S parameter showed a closer variation between the two resonances (11.64 and 12.8 GHz) which signified that a much more accurate measurement of the cotton dielectric constant was possible up to a moisture content of 16.1%. However, certain unwanted changes were noted at 8.4–8.9 GHz and 10.6–12.4 GHz. The proposed triple-band absorber has potential applications in the X band sensing of moisture in capsules or tablet bottles.